Demotivation: The Unseen Side of Vocational High School Students’ Motivation in Learning English - Anis Soviana (Jurnal Pendidikan Humaniora, 2018)
Abstract: This descriptive qualitative study aimed to investigate the demotivating factors experienced by vocational high school students in learning English. Nineteen students of Department of Graphic Production students of SMKN 4 Malang were involved as research participants. The findings revealed that the students experienced both internal and external demotivation. External demotivation was more dominant compared to internal demotivation. External demotivation fell into four themes—i.e., teacher’s behaviour and compenetence, teacher’s teaching method, learning environment, and the materials of English lesson; while internal demotivation fell into three themes—i.e., students’ attitude toward English, students’ experience of failure, and students’ self-esteem. It is suggested that teacher should improve their awareness of this phenomenon and expected that proper treatment from the teacher can minimize students’ demotivation in learning English. Key Words: demotivation, demotivating factors, internal demotivation, external demotivationAbstract: Penelitian deskriptif kualitatif ini bertujuan untuk menemukan faktor-faktor penyebab demo-tivasi siswa dalam belajar Bahasa Inggris. Penelitian melibatkan 19 siswa SMKN 4 Malang Jurusan Produksi Grafika sebagai partisipan. Hasil penelitian menunjukkan bahwa siswa Produksi Grafika mengalami demotivasi dalam belajar Bahasa Inggris baik berupa demotivasi internal maupun demotiva-si eksternal. Demotivasi eksternal lebih dominan dialami siswa dibandingkan dengan demotivasi eksternal. Untuk demotivasi eksternal meliputi: kompetensi dan tingkah laku guru, metode guru da-lam mengajar, lingkungan belajar, dan materi Bahasa Inggris yang dipelajari. Sedangkan demotivasi internal meliputi: pandangan siswa tentang Bahasa Inggris, pengalaman siswa ketika mengalami ke-gagalan dalam belajar Bahasa Inggris, dan kepercayaan diri siswa. Melalui penelitian ini, disarankan agar para guru lebih memperhatikan fenomena ini. Perlakuan yang tepat dari guru diharapkan dapat meminimalisi demotivasi yang dialami siswa dalam belajar Bahasa Inggris.Kata kunci: demotivasi, faktor demotivasi, demotivasi internal, demotivasi eksternal